2018
DOI: 10.1016/s2468-2667(18)30025-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-level lead exposure and mortality in US adults: a population-based cohort study

Abstract: The Artemis Fund and Simon Fraser University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
344
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 438 publications
(359 citation statements)
references
References 26 publications
9
344
2
4
Order By: Relevance
“…Interestingly, other studies have reported the associations between blood lead and periodontitis,26 cardiovascular disease27 and chronic kidney disease28 to similarly be present only among non-smokers. It is unclear what biological mechanism would underlie this finding.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, other studies have reported the associations between blood lead and periodontitis,26 cardiovascular disease27 and chronic kidney disease28 to similarly be present only among non-smokers. It is unclear what biological mechanism would underlie this finding.…”
Section: Discussionmentioning
confidence: 98%
“…The toxicity of lead (Pb) is widely recognized; lead has been linked to childhood neurological impairment (Lanphear et al, 2005;Needleman & Gatsonis, 1990;Tong et al, 2000;World Health Organization, 2010) and cardiovascular disease later in life (Lanphear et al, 2018;Navas-Acien et al, 2007). Children under the age of 6 are at highest risk of Pb exposure as they explore their environment by crawling on the ground and placing dusty toys and hands into their mouths.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation is most pronounced for children and carrying women. For Americans, elevated lead levels is estimated to be an attributable mortality factor for more than 400 000 deaths annually . Such concerns are highly relevant for the working conditions and toxic local environment at lead smelters in producing countries …”
Section: Introductionmentioning
confidence: 99%